Numerical Simulation of Full-Scale Three-Dimensional Fluid Flow in an Oscillating Reactor - Gong, Houjun; Wu, Mengqi (Frontiers in Energy Research, 2021)
Marine reactors are subjected to additional motions due to ocean conditions. These additional motions will cause large fluctuation of flow rate and change the coolant flow field, making the system unstable. Therefore, in order to understand the effect of oscillating motion on the flow characteristics, a numerical simulation of fluid flow is carried out based on a full-scale three-dimensional oscillating marine reactor. In this study, the resistance coefficients of the lattice, rod buddle and steam generator are fitted, and the distribution of flow rate, velocity as well as pressure in different regions is investigated through the standard model. After additional oscillation is introduced, the flow field in an oscillating reactor is presented and the effect of oscillating angle and elevation on the flow rate is investigated. Results show that the oscillating motion can greatly change the flow field in the reactor; most of the coolant circulates in the downcommer and lower head with only a small amount of coolant entering the core; the flow fluctuation period is consistent with the oscillating period, and the flow variation patterns under different oscillating conditions are basically the same; since the flow amplitude is related to oscillating speed, the amplitude of flow rate rises when decreasing the maximum oscillating angle; the oscillating elevation has little effect on the flow rate.